The price of access the willingness to pay for broadband connectivity of rural households in Brgy. Guinsorongan, Catbalogan City - Patata, Eman C.; Pormon, Miah Maye M. (2016)
Access to internet has been increasing in the present, wherein many consumers and businesses rely on this to get information and transmit data. However, rural communities are lagging behind urban areas in broadband access and adoption rates, due to high transaction costs and perhaps profitless installation for the provider. The respondents of the study are the households of Brgy. Guinsorongan, Catbalogan City. This study investigates the usage behavior, perceptions and attitudes of the household consumers towards internet. It also seeks to determine the willingness to pay for internet services and through ordinal logistic regression, identify the significant factors that affect their willingness to pay for such service.
Results suggest that social media and school-related research are the major activities done by the household users. Generally, it shows that households have slightly positive attitudes and perceptions on the use of internet and on the technology itself with its usefulness as a core weight for this conclusion. However, willingness to pay for internet services seems to be at the lowest bracket (Php 1499 at most) and their perception of low quality internet services in the area, apart from household income, has been an important factor for this valuation. ISPs should therefore adopt business models that provide affordable and reliable connections. Policies toward digitization should focus on the rural countryside, in order to help the "unconnected" raise enough awareness on the benefits and applications of the technology.
Undergraduate thesis (B.A.S.S. Economics) -- University of the Philippines, Tacloban.
Keywords: Social Sciences